Budaya & Kearifan Lokal dalam Pendidikan: Praktik Mencuci Kaki Orang Tua di SD Bina Bakti Kubu Raya - Rahmat, Didi; Wahyudi, Hijrah; Barata, Juliahir; Mardiyati (Khidmatuna: Jurnal Pengabdian Masyarakat, 2025)
This PkM activity explores culture & local wisdom in education through the practice of washing parents' feet at Bina Bakti Elementary School in Kubu Raya. This tradition serves not only as a symbol of respect but also as a medium for imparting moral and ethical values to students. In the community context, washing parents' feet symbolizes gratitude and recognition of the sacrifices and contributions parents make in educating their children. The research methods used include observation and interviews involving students, parents, and teachers. The findings indicate that this practice is effective in building students' character, enhancing discipline, and strengthening intergenerational relationships. Furthermore, this tradition fosters a positive and respectful school environment. By integrating culture & local wisdom into the educational curriculum, Bina Bakti Elementary School not only preserves culture but also instills essential values crucial for children's development. This research is expected to provide insights for educators and stakeholders to explore and leverage culture & local wisdom in the learning process.